« C’était une femme à qui il fallait un époux et lui un homme qui voulait une épouse… ». Les représentations filmographiques des mariages par correspondance - Laure Sizaire; Gwenola Ricordeau (Genre, Sexualité et Société)
The analysis of an eight film corpus of post-1945 movies staging a mail-order marriage shows their shared narrative in three social and historic contexts (colonization, migration and globalization of the marriage market): marriage resolves the problems faced by men due to shortage of women. Despite the various historic eras and the diversity of the marriages (either endogamous or exogamous) staged in films, men and women are represented as opposed and complementary. In addition, the studied films suggest social fantasies about romantic love and norms regarding marriage and money. But they also highlight how the “arrangement of the sexes” organized by marriage can be subverted by women through international matchmaking and marriages.